2016
DOI: 10.1186/s13075-016-1187-7
|View full text |Cite
|
Sign up to set email alerts
|

Smad-dependent mechanisms of inflammatory bone destruction

Abstract: Homeostatic bone remodelling becomes disturbed in a variety of pathologic conditions that affect the skeleton, including inflammatory diseases. Rheumatoid arthritis is the prototype of an inflammatory arthritis characterised by chronic inflammation, progressive cartilage destruction and focal bone erosions and is a prime example for a disease with disturbed bone homeostasis. The inflammatory milieu favours the recruitment and activation of osteoclasts, which have been found to be the cells that are primarily r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 115 publications
2
33
0
Order By: Relevance
“…This difference in p-values between ES/BS and OV/BV might suggest that bone erosion exceeds osteoid formation in CD109 −/− mice. Together with previous studies showing that CD109 is a negative regulator of TGF-β signaling (Finnson et al, 2006;Hagiwara et al, 2010;Sunagawa et al, 2016;Zhang et al, 2015), our hypothesis is that CD109 deficiency induces aberrations in bone metabolism in vivo via TGF-β signaling (Asagiri & Takayanagi, 2007;Edwards et al, 2010;Fennen, Pap, & Dankbar, 2016;Gingery et al, 2008;Itonaga et al, 2004), whereas CD109 may regulate osteoclastogenesis by a mechanism independent of TGF-β signaling in vitro (Wang et al, 2013). Notably, this suggests that CD109 −/− mice might be useful as an alternative osteoporosis animal model that requires no procedures such as ovariectomy, orchiectomy, hindlimb immobilization or calcium-restricted diet (Miller, Bowman, & Jee, 1995).…”
Section: Discussionsupporting
confidence: 83%
“…This difference in p-values between ES/BS and OV/BV might suggest that bone erosion exceeds osteoid formation in CD109 −/− mice. Together with previous studies showing that CD109 is a negative regulator of TGF-β signaling (Finnson et al, 2006;Hagiwara et al, 2010;Sunagawa et al, 2016;Zhang et al, 2015), our hypothesis is that CD109 deficiency induces aberrations in bone metabolism in vivo via TGF-β signaling (Asagiri & Takayanagi, 2007;Edwards et al, 2010;Fennen, Pap, & Dankbar, 2016;Gingery et al, 2008;Itonaga et al, 2004), whereas CD109 may regulate osteoclastogenesis by a mechanism independent of TGF-β signaling in vitro (Wang et al, 2013). Notably, this suggests that CD109 −/− mice might be useful as an alternative osteoporosis animal model that requires no procedures such as ovariectomy, orchiectomy, hindlimb immobilization or calcium-restricted diet (Miller, Bowman, & Jee, 1995).…”
Section: Discussionsupporting
confidence: 83%
“…SMAD protein family belongs to the intracellular signaling protein, which was first identified in invertebrates by gene screening [19]. Studies have shown that the SMAD protein family plays a key role in bone formation [20,21]. Smad3 is a member of the SMAD protein family, which has been proved to be a critical factor in the normal maintenance of the bone [22].…”
mentioning
confidence: 99%
“…For example, mice grown with FST overexpression via global knock-in exhibited an impaired bone structure (43). However, in adult diabetic mice, FST was shown to accelerate bone regeneration by inhibiting myostatin-induced osteoclastogenesis (44,45). Furthermore, it has been reported that FST down-regulates BMP2-driven osteoclast activation (46).…”
Section: Discussionmentioning
confidence: 99%